1994
DOI: 10.1136/adc.70.3.187
|View full text |Cite
|
Sign up to set email alerts
|

Thermal balance and metabolic rate during upper respiratory tract infection in infants.

Abstract: Sequential recordings were made in the first five months after birth of metabolic rate, environmental temperature, and body temperature during sleep at home in 17 infants, each with an older sibling. Further recordings were made whenever an older sibling developed an upper respiratory tract infection (URTI), again four to six days later, and again two weeks later, aiming to achieve recordings before, during, and after an URTI in the infant. The temperature of the room and wrapping of the infant were determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 11 publications
3
14
0
Order By: Relevance
“…The values obtained were very similar to those previously reported for infants of similar ages (14,15,17,21).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The values obtained were very similar to those previously reported for infants of similar ages (14,15,17,21).…”
Section: Resultssupporting
confidence: 90%
“…1). This gave an overall predicted effective thermal resistance (taking account of body surface area covered) for clothing and sleeping bag of approximately 3.3 tog (excluding diaper), which from our previous studies (14–16) we calculated would provide a thermoneutral environment with a room temperature above 19–20°C. (The tog value of a fabric is defined as 10 times the temperature difference in degree centigrade between its two faces when the heat flow is equal to 1 W/m 2 ) (14).…”
Section: Methodsmentioning
confidence: 99%
“…It is also the site for several neurotransmitter abnormalities in SIDS, including in 5-HT, muscarinic, and kainate receptor binding [21, 3234]. It is well documented that CO 2 levels are elevated during severe neonatal infection [2] and, interestingly, even mild upper respiratory infection may increase CO 2 levels in infants over 3 months of age [9]. Animal studies indicate that the CO 2 elevation can be attributed to a hyper-metabolic state induced by proinflammatory cytokines [15].…”
Section: Discussionmentioning
confidence: 99%
“…A major site of 5-HT cell bodies in the human infant brainstem is in the arcuate nucleus, the putative site for central carbon dioxide (CO 2 ) sensitivity in humans and animal models [10, 26, 30, 37]. In this regard, the synergistic effect of prone sleeping and infection on SIDS risk may be a “set-up” for CO 2 accumulation, as both rebreathing in the face-down (prone) position and increased metabolism due to infection may increase CO 2 levels [2, 9, 18, 51]. Death may be triggered if CO 2 -sensing regions in the brainstem, such as the arcuate nucleus, are compromised and cannot mount an arousal response to protect the infant from the dangerous situation.…”
Section: Introductionmentioning
confidence: 99%
“…A third alternate explanation of age of death in SIDS suggested by Fleming et al, 34 involves heat stress. They found that younger infants with upper respiratory infections rarely developed a fever, compared with infants older than 3 months, who also had higher metabolic rates even without a fever, thus subjecting the infants beyond one month of age to greater vulnerability to heat stress and SIDS.…”
Section: Critical Developmental Period In Homeostatic Controlmentioning
confidence: 99%